Interaction of lateral cracks in double scratching of single-crystal silicon carbide. (December 2019) - Wang, Peizhi; Ge, Peiqi; Bi, Wenbo; Meng, Jianfeng
Highlights: A new method is established to analyze the interaction of lateral cracks in double scratching of SiC. Stress field and stress intensity factors of lateral cracks are calculated. Effects of indenter angle, scratching depth and separation distance on interaction are discussed. Abstract: In this paper, a new method is established to analyze the interaction of lateral cracks in double scratching process, which is a basic problem in machining of single-crystal silicon carbide. Applying superposition principle, this interaction problem is reduced to the calculation of stress intensity factors (SIFs) around two scratching-induced collinear cracks under scratching-induced stress field. First, values of SIFs at crack tips under the scratching-induced stress field are obtained applying Fourier transformation, gap functions of displacements and Jacobi polynomials. Then, the scratching-induced stress filed is obtained by the superposition of Boussinesq field, Cerruti field and Blister stress field. Finally, this calculation method is verified by comparing with the results in literature in special case. It is found that values of SIFs decrease dramatically when scratching separation distance increases. The interaction effect can be neglected when the separation distance is larger than 1.6 times of the length of lateral cracks generated in single scratching.